Combined effect of molybdenum and nitrogen fertilization on nitrogen metabolism and amino acid content in tobacco leaves - Sun, Jingguo; Zhao, Youyou; Qin, Xiaoming; Hu, Zhenlan; Li, Jianping; Guo, Yali; Sun, Guangwei; Chen, Zhengguo; Huang, Hong; Hu, Chengxiao; Sun, Xuecheng (Frontiers in Agronomy, 2024)
IntroductionThis study investigated the combined effects of molybdenum (Mo) and nitrogen (N) fertilization on N metabolism and amino acid content in the leaves of flue-cured tobacco (Nicotiana tabacum L.) during its mature stage through a pot experiment.MethodsDifferent application levels of Mo (0, 0.15, 0.30 mg/kg soil) and N (0.06, 0.24, 0.42 g/kg soil) were set to observe and analyze changes in leaf quality, N, and amino acid content in the tobacco plants.ResultsThe results revealed that the N fertilizer application level exhibited a primary effect on regulating the total nitrogen, nitrate nitrogen, soluble protein, and amino acid nitrogen concentrations within tobacco leaves, while the effectiveness of Mo fertilization was influenced by the level of N applied. Specifically, under the conditions of 0.24 g/kg soil N and 0.30 mg/kg soil Mo application, the N content, N accumulation, and dry matter mass of the tobacco plants increased significantly by 110%, 204%, and 48%, respectively. Concurrently, nitrate reductase activity increased by 107-fold, and the nitrate nitrogen content was relatively low, contributing to enhanced tobacco yield and safety. Moreover, this treatment led to a notable (170%) increase in free amino acid nitrogen content, with minimal impact on total amino acids and soluble proteins. Notably, it effectively increased the content of free amino acids beneficial to the sensory quality of tobacco (such as histidine, arginine, aspartic acid, isoleucine, and glutamic acid) without reducing the total amino acid content, while simultaneously reducing other amino acids that might affect quality. Therefore, the combined application of 0.30 mg/kg soil Mo and 0.24 g/kg soil N specifically optimized the amino acid composition in tobacco leaves, positively impacting overall quality and market competitiveness.DiscussionThis study provides a theoretical basis for the rational application of Mo fertilizer in Mo-deficient areas to improve the yield and quality of flue-cured tobacco.